2005
DOI: 10.1093/sleep/28.8.955
|View full text |Cite
|
Sign up to set email alerts
|

SPECT Findings in the Kleine-Levin Syndrome

Abstract: Hypoperfusion of the thalamus is a consistent finding during the symptomatic period, but perfusion abnormalities may persist even during the asymptomatic period. The longer the duration of the syndrome, the more extended the hypoperfusion regions during the asymptomatic period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
75
2
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(89 citation statements)
references
References 0 publications
10
75
2
2
Order By: Relevance
“…Evidence for thalamic involvement also exists; Tc-99m ethyl cysteinate dimer (ECD) single-photon emission CT analysis during symptomatic periods of KLS has demonstrated thalamic hypoperfusion (Huang et al 2005;Hong et al 2006;Huang et al 2012b;Kas et al 2014). MRI assessment of PANDAS youth has demonstrated enlarged basal ganglia (Giedd et al 1996(Giedd et al , 2000, and positron emission tomography has demonstrated increased activated microglial cells, which are suggestive of neuroinflammation, in bilateral caudate nuclei and bilateral lentiform in youth with PANDAS (Kumar et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for thalamic involvement also exists; Tc-99m ethyl cysteinate dimer (ECD) single-photon emission CT analysis during symptomatic periods of KLS has demonstrated thalamic hypoperfusion (Huang et al 2005;Hong et al 2006;Huang et al 2012b;Kas et al 2014). MRI assessment of PANDAS youth has demonstrated enlarged basal ganglia (Giedd et al 1996(Giedd et al , 2000, and positron emission tomography has demonstrated increased activated microglial cells, which are suggestive of neuroinflammation, in bilateral caudate nuclei and bilateral lentiform in youth with PANDAS (Kumar et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The exact pathogenesis is not completely understood. A disorder of the diencephalon with episodic diffuse brain hypoperfusion, a viral aetiology due to associated flu like symptoms or autoimmune basis due to association with certain HLA types are postulated [2,3].…”
Section: Research Lettersmentioning
confidence: 99%
“…Structural neuroimaging and interepisodic EEG are usually normal. However, functional neuroimaging (Engström et al, 2009;Engström et al, 2013;Dauvilliers et al, 2014;Hong et al, 2006;Huang et al, 2005) and a few post mortem studies (Arnulf et al, 2005) indicate frontotemporal dysfunction and possible thalamic pathology. In functional magnetic resonance imaging (fMRI) studies, we have previously shown that KLS patients have thalamic hyperactivation when challenged with a working memory task (Engström et al, 2009;Engström et al, 2013).…”
Section: Introductionmentioning
confidence: 99%